Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.analchem.2c03055
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent Nanogels as Intensive and Stable Signal Probes for Fast Immunoassay of SARS-CoV-2 Nucleocapsid Protein

Abstract: It is highly desired to exploit good nanomaterials as nanocarriers for immobilizing chemiluminescence (CL) reagents, catalysts and antibodies to develop signal probes with intensive and stable CL properties for immunoassays. In this work, N-(4-aminobutyl)-N-ethylisoluminol (ABEI) and Co2+ bifunctionalized polymethylacrylic acid nanogels (PMAANGs-ABEI/Co2+) were synthesized via a facile strategy by utilizing carboxyl group-rich PMAANGs as nanocarriers to immobilize ABEI and Co2+. The obtained PMAANGs-ABEI/Co2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…34 Some other reagents have to be introduced on these materials to facilitate antibody modification. 35,36 For CAACo, ABEI and Co 2+ were embedded in the pores of Au-COF, and antibodies could conjugate with CAACo directly through Au−N and Au−S bonds. Different combinations of CL reagents and metal ions were involved in investigating the universality of this method to prepare different CL reagents and metal ion-functionalized Au-COFs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Some other reagents have to be introduced on these materials to facilitate antibody modification. 35,36 For CAACo, ABEI and Co 2+ were embedded in the pores of Au-COF, and antibodies could conjugate with CAACo directly through Au−N and Au−S bonds. Different combinations of CL reagents and metal ions were involved in investigating the universality of this method to prepare different CL reagents and metal ion-functionalized Au-COFs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, it is reported that the other CL-functionalized materials are difficult to conjugate antibodies directly since the binding sites were occupied by CL molecules and metal ions . Some other reagents have to be introduced on these materials to facilitate antibody modification. , For CAACo, ABEI and Co 2+ were embedded in the pores of Au-COF, and antibodies could conjugate with CAACo directly through Au–N and Au–S bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Chemiluminescence (CL) is a phenomenon wherein excited molecules, produced through a chemical reaction, release light upon returning to the ground state . Offering simplicity in equipment, high sensitivity, and a broad linear range, CL has found extensive applications in the detection of ions and small molecules, immunoassay, imaging, nucleic acid detection, etc. Luminol, recognized as a typical lumiphore, has gained popularity due to its water solubility, stability, and cost-effectiveness. , However, the low CL efficiency of the classical luminol/hydrogen peroxide (H 2 O 2 ) system has greatly limited their wide development in analytical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In CL, since external light sources or optics are not required for sample radiation, as they are in other analytical methods such as fluorescence, problems such as photobleaching, source instability, and system complexity can be drastically reduced . Due to the extremely high sensitivity and suitability for miniaturization, , CL has proved to be a superior analytical tool for the detection and quantification of a wide variety of biological materials, including amino acids, , proteins, , DNA, , RNA, heavy metals, , and other analytes. Furthermore, by utilizing existing surface modification techniques to preimmobilize reaction reagents on the reaction zone, multiplex CL determination can be easily achieved, , including those on paper-based analytical devices (PADs), which are highly suitable for low-cost assays at the point-of-need, such as in the field or in resource-constrained settings . For instance, Cui’s group developed a three-dimensional microfluidic paper-based device (3D μPAD), on which a unique time-resolved platform was developed to achieve simultaneous detection of three different biomarkers of early acute myocardial infarction .…”
Section: Introductionmentioning
confidence: 99%